2014
DOI: 10.1890/es13-00302.1
|View full text |Cite
|
Sign up to set email alerts
|

The trophic role of a forest salamander: impacts on invertebrates, leaf litter retention, and the humification process

Abstract: Abstract. Woodland (Plethodontid) salamanders are the most abundant vertebrates in North American forests, functioning as predators on invertebrates and prey for higher trophic levels. We investigated the role of Ensatina (Ensatina eschscholtzii ) in regulating invertebrate numbers and leaf litter retention in a northern California forest. Our objective was to examine how salamander predation on invertebrates affects leaf litter retention and the amount available for soil-building and carbon capture at the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 51 publications
5
78
0
Order By: Relevance
“…Terrestrial leaf litter amphibians are important predators in the leaf litter environment and play a crucial role in nutrient cycling, energy flow, and carbon storage of forest ecosystems (Davic andWelsh 2004, Best andWelsh 2014). Their importance stems from high population densities and efficiency at converting invertebrate biomass to vertebrate biomass (Best and Welsh 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Terrestrial leaf litter amphibians are important predators in the leaf litter environment and play a crucial role in nutrient cycling, energy flow, and carbon storage of forest ecosystems (Davic andWelsh 2004, Best andWelsh 2014). Their importance stems from high population densities and efficiency at converting invertebrate biomass to vertebrate biomass (Best and Welsh 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their importance stems from high population densities and efficiency at converting invertebrate biomass to vertebrate biomass (Best and Welsh 2014). Moisture is a key factor regulating leaf litter predator-prey dynamics (Walton 2013), and variable rainfall has been shown to alter the invertebrate prey base of leaf litter amphibians (Levings and Windsor 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their exceptionally abundant biomass, amphibians are known to greatly influence nutrient cycling [3][4][5] and leaf-litter food webs [2]. Furthermore, salamanders are important for structuring invertebrate communities in primary stream [5,6] and forested [7,8] environments, sequestering forest carbon stocks [8], and providing a significant and nutritious prey source for other predators [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the importance of salamanders in food webs and their contribution to nutrient cycling (Walton et al 2006, Best andWelsh 2014) and carbon sequestration (Best and Welsh 2014). Given their physiological requirements, they are generally very sensitive to habitat disturbance (deMaynadier and Hunter 1995).…”
Section: Introductionmentioning
confidence: 99%